The Perspectives of Classical and Contemporary Islamic Scholars on the Phenomenon of Suicide in the Modern Era - Baiq Ulfa Azizah (Journal of Islamic Religious Studies, 2026)
Suicide has become a complex global phenomenon involving psychological, social, medical, and religious dimensions, requiring interdisciplinary understanding and prevention strategies. From an Islamic perspective, suicide is not only a mental health issue but also a theological and ethical concern. This study aimed to examine and compare the perspectives of classical and contemporary Islamic scholars on suicide in the modern era, focusing on conceptual foundations, interpretive differences, and implications for prevention. The research employed a qualitative approach using library research combined with comparative analysis. Data were collected from classical Islamic texts, contemporary scholarly publications, and interdisciplinary literature related to psychology, sociology, and mental health. The data were analyzed using thematic and comparative techniques to identify patterns, similarities, and differences across historical perspectives. The findings indicate that classical scholars consistently conceptualized suicide as a major sin within theological and juridical frameworks, emphasizing the sanctity of life and divine sovereignty. Contemporary scholars maintain this doctrinal foundation but increasingly incorporate psychological suffering, social pressures, and mental health considerations, reflecting interdisciplinary integration. The study also reveals that religiosity functions both as a protective factor and, in certain contexts, as a barrier due to stigma surrounding mental health. The integration of classical ethical teachings with contemporary scientific approaches provides a holistic framework for suicide prevention that addresses spiritual, psychological, and social dimensions simultaneously. The study concludes that classical and contemporary perspectives are complementary and can contribute to culturally sensitive prevention strategies in Muslim societies while demonstrating the adaptability of Islamic intellectual tradition in responding to modern challenges.